The Factors of Determining Repayment Performance in Individual Loan for Small Medium Enterprises in Indonesia - Lailiya Rohmana; Permata Wulandari (Eduvest - Journal of Universal Studies, 2024)
This study aims to determine the affecting factors of repayment performance in Small Medium Enterprises (SMEs) in Indonesia for individual loan program. The data in this study is gathered by credit active during 2023 which contain of 300 samples from several region in Indonesia that came from one of Non-Banking Financial Institutions (NBFIs). The data is analyzed by logit regression model by Stata software version 18. The study indicates that the borrower’s income and amount of loan disbursements have significantly affected the repayment of the borrower’s outstanding loan for both principal and interest in time. Furthermore, the study shows that the higher amount of loan disbursement might affect the lower probability of defaulting due to high assessment of credit appraisal. Since the loan programs are delivered for individual for owner or management of Small Medium Enterprises (SMEs) in Indonesia. A prudent procedure is needed to establish for newer borrowers of the individual loan programs. The screening process consists of income cash flow analysis and how long the cash flow will be generated for repaying the programs. the novelty for this result enhances the current research for SMEs financing program in Indonesia for individual loan credit program. Specially credit loan program is delivered and sponsored by Indonesia government. Not much research focused on individual loan programs for SME’s owner or management.